Linguistic Landscape on Coffee Shop Signboards in Medan - Soraya Tsamara Zahra; Eddy Setia; Thyrhaya Zein (Budapest International Research and Critics University, 2021)
Linguistic Landscape (LL) is a study that focuses on the use of language in public spaces, whether monolingual, bilingual, or multilingual. The growth of coffee shops in the city of Medan is increasing due to the increasing development of coffee consumption so that it appears around the Ringroad road which reflects its uniqueness and various different racial backgrounds.This research deals with the linguistic landscape and the use of certain languages on coffee shop signage. The purpose of this study was to determine the use of language in language in public spaces, to explain the characteristics used on coffee shop signboards and the reasons why shop owners chose a particular language in naming coffee shops. This research method is qualitative by applying the data collection of coffee shop signage. Methods of data collection is done by observation, interviews, documentation. Methods of data analysis with data collection, data condensation, data display and drawing conclusions. The results showed that the researchers found 12 languages, namely: Acehnese, Batak, and Javanese, Indonesian, English, Japanese, Italian, Arabic, French, Vietnamese, Spanish, and Bugis languages. It was found that the language between English and Indonesian is more dominant than other languages. The characteristics on the 89 nameplates tend to be the same. The reasons for shop owners in choosing a particular name are the type of coffee, culture, place/location, easy to remember and simple, family, reference, social time, ownership, promotion, personal, hope, leadership, heredity, recklessness, uniqueness, love of coffee, art, products, regional specialties, fondness for foreign languages. Language in public spaces and the phenomenon of language is of great interest to researchers, especially linguists.